Stock Price Volatility and Policy Bailout: Evidence from Growth Enterprise Market in China - Chi, Qishui; Wang, Songtao (Archives of Business Research, 2018)
Growth enterprises in China have been increasing their paces to raise capital through Growth Enterprise Market (GEM) since October, 2009. Based on mass Monte Carlo simulation, this article utilizes multi break structural change method to examine the fluctuation characteristics of GEM stock index in China. This study indicates that time series of Chinese GEM stock index are not characterized by mean reversion. Therefore, the policy bailouts in the market including the rescue package of the government in June 2015 are ineffective because they are already offset by other factors. The long-run growth of GEM stock index depend on the supply and demand situation in capital market as well as the growth of national economy but has no connection with the policy bailouts. The results provide policies making guidance on GEM in China with empirical evidence.